LINGKUNGAN DALAM KAJIAN AL-QUR`AN: KRISIS LINGKUNGAN DAN PENANGGULANGANNYA PERSPEKTIF AL-QUR`AN - Qomarullah, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2014)
Human as caliph on earth, God entrusted the earth to maintain and preserve it, whether at sea, on earth and in the air. God gave humans an important role and hand over full land and surrounding environment to create in accordance with its role as a representative of God. The problem that arises is that the human representative of God on earth as it does not implement the mandate to protect the environment, such as illegal logging, global warming damage that arises is in the heavens and on earth, in the sea and on land. The picture is already contained in the Quran about the damage this natural phenomenon caused by human hands. Thus, the existence of man as a vicegerent on earth stake to keep this planet.